Associação entre distúrbio de voz e alteração da respiração em crianças - Oliveira, Cristiane Marangom de (2011)
Introduction: Children are immersed in noisy and competitive environments, and are thus subject to developing vocal disorders. Therefore, this is the best moment to identify possible disorders in an early stage, and to plan actions which promote healthy communication habits, focusing on vocal well-being. However, there has been little emphasis on voice disorders associated to breathing in children. Aim: To analyze the association between vocal disorder and respiratory mode (lip posture and nasal flow) aspects in children, according to sex. Methods: 250 children in between six and nine years of age were selected from a public school in the city of São Paulo. The collected data consisted of a spontaneous speech sample and the retelling of a story base don a picture-book. Computer software Audacity and a headset microphone were used for voice recording. The children s respiratory mode was analyzed according to lip posture while producing a drawing, and the nasal flow was assessed using a Glatzel mirror. Lip posture disorder was considered when the lips where part-time open and part time closed, and also when they remained open or partly open. Nasal flow disorder was characterized by reduced flow or nasal obstruction. Three judges who were speech-language pathologists specialized in voice listened to the recordings and performed a perceptual-auditory assessment of the children s vocal qualities using the GIRBAS scale. Voice disorder was characterized by general grade (G) 2 and 3 (moderate or intense). The results were submitted to statistical analysis and associated using the chi-square test (p≤0.05). Results: Of the 250 children, 126 (50,4%) were female, and 124 (49,6%) were male. As for the General Grade (G), 32 (12,8%) had vocal quality disorders, and these were 16 (6,4%) males, and 16 (6,4%) females. For the variable respiratory mode, 92 (36,8%) children had lip posture disorders. Of these, 57 (22,8%) were male and 35 (14%) were female. 178 (71.2%) children had nasal flow disorders, 91 (36,4%) male, and 87 (34,8%) females. There was no statistical association between voice disorder and variables sex (p= 0,96), lip posture (p=0,38) and nasal flow (p=0,18), or between nasal flow disorder and sex (p=0,449). The association between lip posture and sex proved to be statistically significant in favor of males (p=0,003). Conclusion: There was no association between vocal and breathing disorders. When considering lip posture disorders, there was a statistically significant association with male children